The Charlotte Project: Recommendations for patient-reported outcomes and clinical parameters in Dravet syndrome through a qualitative and Delphi consensus study - Aledo-Serrano, Ángel; Mingorance, Ana; Villanueva, Vicente; García-Peñas, Juan José; Gil-Nagel, Antonio; Boronat, Susana; Aibar, JoséÁngel; Cámara, Silvia; Yániz, María José; Aras, Luis Miguel; Blanco, Bárbara; Sánchez-Carpintero, Rocío (Frontiers in Neurology, 2022)
Objective: The appropriate management of patients with Dravet Syndrome (DS) is challenging, given the severity of symptoms and the burden of the disease for patients and caregivers. This study aimed to identify, through a qualitative methodology and a Delphi consensus-driven process, a set of recommendations for the management of DS to guide clinicians in the assessment of the clinical condition and quality of life (QoL) of DS patients, with a special focus on patient- and caregiver-reported outcomes (PROs). Methods: This study was conducted in five phases, led by a multidisciplinary scientific committee (SC) including pediatric neurologists, epileptologists, a neuropsychologist, an epilepsy nurse, and members of DS patient advocates. In phases 1 and 2, a questionnaire related to patients’ QoL was prepared and answered by caregivers and the SC. In phase 3, the SC generated, based on these answers and on a focus group discussion, a 70-item Delphi questionnaire, covering six topic categories on a nine-point Likert scale. In phase 4, thirty-two panelists, from different Spanish institutions and with a multidisciplinary background, answered the questionnaire. Consensus was obtained and defined as strong or moderate if ≥80% and 67%–79% of panelists, respectively, rated the statement with ≥7. Phase 5 consisted of the preparation of the manuscript. Results: The panelists agreed on a total of 69 items (98.6%), 54 (77.14%) and 15 (21.43%) with strong and moderate consensus, respectively. The experts’ recommendations included the need for frequent assessment of patient and caregivers QoL parameters. The experts agreed that QoL should be assessed through specific questionnaires covering different domains. Likewise, the results showed consensus regarding the regular evaluation of several clinical parameters related to neurodevelopment, attention, behavior, other comorbidities, and sudden unexpected death in epilepsy (SUDEP). A consensus was also reached on the instruments, specific parameters, and caregivers’ education in the routine clinical management of patients with DS. Conclusions: This consensus resulted in a set of recommendations for the assessment of clinical and QoL parameters, including PROs, related to the general evaluation of QoL, neurodevelopment, attention, behavior, other comorbidities affecting QoL, SUDEP, and QoL of caregivers/relatives and patients with DS.